MFI and FAU-Type Zeolites as Trapping Materials for Light Hydrocarbons Emission Control at Low Partial Pressure and High Temperature - Fortunato Migliardini; Fabio Iucolano; Domenico Caputo; Pasquale Corbo (Journal of Chemistry)
The adsorption of light hydrocarbons (C2–C5 olefins and paraffins, toluene) on HZSM-5, silicalite, and HY was studied for application in treatment of exhaust streams of the petrochemical industry and of vehicles under cold start conditions. At this aim the trapping capability was evaluated on hydrated zeolites by breakthrough curves at low hydrocarbon partial pressure (0-1 kPa), in the temperature range 298–523 K and at space velocity of 30000 h−1. The basic adsorption properties of materials were also verified for three selected hydrocarbons (ethylene, isobutene, and toluene) by equilibrium isotherms on dehydrated zeolites at 298 K. The role of physicochemical characteristics of adsorbent materials was discussed in relation with their trapping capability of different types of hydrocarbons.